2018
DOI: 10.14710/jitaa.43.2.131-139
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hatchery waste meal in ration on nutrient retention and performances of laying quails

Abstract: The objective of this study was to investigate the effect of hatchery waste meal (HWM) as a whole or without shell (shell-less) in the diet on nutrient retention and performance of quails. The study used 500 female quails (Coturnix coturnix japonica) aged 30 days with an average initial body weight of 94.75±4.17 gr. The quails were randomly allocated to five dietary treatments in a completely randomized design with 5 replicates of 20 quails. The dietary treatments were: Control = basal diet, Whole 4% = 96% bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The high-fat content of IEP may ease digestion along the intestine, allowing for optimal nutrient digestion and absorption (Nutrition Research Council, 1994). Previous studies have con rmed that EE digestibility increased when diets were supplemented with increased EE content (Pesti et al, 1986;Indreswari and Ratriyanto, 2018). Similarly, increasing dietary EE content enhances ME (Sathishkumar and Prabakaran, 2008;Indreswari and Ratriyanto, 2018).…”
Section: Nutrient Digestibilitymentioning
confidence: 92%
See 1 more Smart Citation
“…The high-fat content of IEP may ease digestion along the intestine, allowing for optimal nutrient digestion and absorption (Nutrition Research Council, 1994). Previous studies have con rmed that EE digestibility increased when diets were supplemented with increased EE content (Pesti et al, 1986;Indreswari and Ratriyanto, 2018). Similarly, increasing dietary EE content enhances ME (Sathishkumar and Prabakaran, 2008;Indreswari and Ratriyanto, 2018).…”
Section: Nutrient Digestibilitymentioning
confidence: 92%
“…Previous studies have con rmed that EE digestibility increased when diets were supplemented with increased EE content (Pesti et al, 1986;Indreswari and Ratriyanto, 2018). Similarly, increasing dietary EE content enhances ME (Sathishkumar and Prabakaran, 2008;Indreswari and Ratriyanto, 2018). Observations in pigs have shown that including dietary spray-dried egg and albumen powder improves amino acid digestibility (Zhang et al, 2015).…”
Section: Nutrient Digestibilitymentioning
confidence: 96%